Pengaruh PAD, Dana Bagi Hasil SDA, dan Jumlah Penduduk terhadap Belanja Daerah dan Pertumbuhan Ekonomi di Kabupaten Kutai Timur - Rusyda, Miftahur; Effendi, Aji Sofyan; Lestari , Diana (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze and determine the effects of Regional Original Revenue (PAD), Revenue Sharing Fund for Natural Resources (DBH SDA), and Population on Regional Expenditure and economic growth in East Kutai Regency. The analysis results indicate that PAD has a positive but insignificant effect on regional expenditure. DBH SDA exhibits a positive and significant influence on regional expenditure. The total population has a positive but insignificant influence on regional expenditure. Furthermore, PAD demonstrates a positive but insignificant influence on economic growth. DBH SDA shows a negative but insignificant influence on economic growth. The total population has a negative but insignificant influence on economic growth. Regional expenditure has a positive but insignificant effect on economic growth. Additionally, PAD positively affects economic growth through regional expenditure. DBH SDA negatively affects economic growth through regional expenditure. The total population negatively affects economic growth through regional expenditure.